Validity and Reliability of a Good Manufacturing Practices Checklist for the Agro‑Biological Industry - Huánuco Azabache, Lucía (2022)
This research presents the design of a checklist or questionnaire for the application of GMP-SSOP during the production of liquid agro-biologicals. Content validation was determined by the judgment of experts belonging to three subsidiaries of a well-known company in the sector, whereas internal consistency was determined with the Kuder‑Richardson KR20 reliability formula. The instrument was established in 210 dichotomous response items distributed in ten dimensions: General, commercial classification, personnel, facilities and equipment, critical support systems, storage area, production area, quality control, documentation, and cleaning and sanitation. It was possible to obtain the applicability consensus of the seven experts and an average KR20 value equal to 0.80. Additionally, all the dimensions presented scores higher than 0.75, which confirmed the validity and reliability of the instrument.